(untitled) (Lex localis - Journal of Local Self-Government, 2025)
In the current piece, Female Complaint Literature and Female Complaint Literature discusses the portrayal of women as victims and/or agents of resistance. Comparisons are made and developed as the study observes the course of female characters in Thomas Heywood’s The First and Second Parts of King Edward IV, Francis Beaumont and John Fletcher’s The Maid’s Tragedy and Thomas Middleton’s The Second Maiden Tragedy throughout the work of these characters: Jane Shore, Aspatia, Evadne and the unnamed Lady. Whereas Jane Shore is an outcast who accepts her lot and pays a price of being a tragic victim of the virtues of obedience, the Jacobean heroines demand acknowledgement of their resistance via verbal opposition, moral uprightness, and, eventually, sacrifice. In the essay, the author states that female suffering serves as a channel to the resistant male-dominated tyranny and patriarchal ideals. Based on feminist and historicist line of criticism, this paper brings out the disruption of these women on the systems that are meant to silence or oppress them. The discussion also suggests the way passivity versus active resistance identifies undergoing ideas about female agency in early modern playwriting. The paper is able to highlight the delicacy of how women responded to oppressive power structures through adopting timely approaches in addressing these situations when they place these female characters in their appropriate contexts in both history and literature. Therefore, the study implies that even amid the realization of tragedy, these characters make their spaces of subversion re-appropriating narrative control in their pain and their decisions.